A Comparative Study on The Level of Cognitive Flexibility Among Higher Secondary Students and Undergraduate Students - John Rehoboth K; Manoj R; Saranya R (International Journal of Indian Psychȯlogy, 2025)
This study was conducted on the comparative levels of cognitive flexibility among higher secondary students (aged 13–18 years) and undergraduate students (aged 18–25 years). Cognitive flexibility is hypothesized that there will be no significant difference between these groups due to the age criteria selected. Using the Cognitive Flexibility Inventory (CFI), the levels of cognitive flexibility assessed among the higher secondary students and undergraduate students. Participants were selected from urban and rural schools and undergraduates to ensure a representative sample, comprising 300 respondents equally divided between higher secondary and undergraduate students. Statistical analysis of t-tests, were conducted to identify significant differences in cognitive flexibility levels between the two groups. The result shows that there is no significant difference in cognitive flexibility between higher secondary and undergraduate students. This shows that cognitive flexibility is rather steady across educational levels, refuting the notion that increased academic exposure considerably improves this cognitive capacity.